2020
DOI: 10.3389/fmed.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy in the Treatment of Dementia: A Systematic Review and Meta-Analysis

Abstract: Background: Dementia is a neurological condition characterized by deterioration in cognitive, behavioral, social, and emotional functions. Pharmacological interventions are available but have limited effect in treating many of the disease's features. Several studies have proposed therapy with music as a possible strategy to slow down cognitive decline and behavioral changes associated with aging in combination with the pharmacological therapy. Objective: We performed a systematic review and subsequent meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 60 publications
1
84
0
2
Order By: Relevance
“…Previous studies have identified some areas that need to be covered to draw clear conclusions on music’s efficacy for PWD. Some of the suggested areas such as combining MT with other activities [ 10 , 47 , 49 ], doing further research and methodological design [ 2 , 14 , 19 , 20 , 21 , 36 , 39 , 46 , 49 ], using a larger sample of randomized clinical trials [ 36 , 40 , 41 , 49 , 50 ], and considering the impact of music on different types and stages of dementia [ 49 ] are aligned with the items that we are going to discuss. Based on our investigation, the following gaps need to be addressed in experiment design and methodologies in future studies to have more reliable and evidence-based results.…”
Section: Gaps In the Researchmentioning
confidence: 99%
“…Previous studies have identified some areas that need to be covered to draw clear conclusions on music’s efficacy for PWD. Some of the suggested areas such as combining MT with other activities [ 10 , 47 , 49 ], doing further research and methodological design [ 2 , 14 , 19 , 20 , 21 , 36 , 39 , 46 , 49 ], using a larger sample of randomized clinical trials [ 36 , 40 , 41 , 49 , 50 ], and considering the impact of music on different types and stages of dementia [ 49 ] are aligned with the items that we are going to discuss. Based on our investigation, the following gaps need to be addressed in experiment design and methodologies in future studies to have more reliable and evidence-based results.…”
Section: Gaps In the Researchmentioning
confidence: 99%
“…The nature and the complexity of the disease require a collaborative approach in the management of patients with dementia (61). A plethora of health care professionals could be involved in the process including dieticians (62), occupational therapists (63), speech therapists (64), music therapists (65), and others. In Greece, a recent health care reform took place with the introduction of integrated health care teams in urban primary care settings (66).…”
Section: Implication For Research Education and Clinical Practicementioning
confidence: 99%
“…Dementia is a chronic disease syndrome characterised by deterioration in memory and thinking, behavioural changes, loss of ability to perform routine tasks, and impaired wellbeing (Draper, 2013). The physical, psychological, social, and economic impacts also affect families, carers, and society ("Dementia", 2019;Moreno-Morales et al, 2020). Most people living with dementia (PLWD) live at home, supported and cared for by their family (Dickinson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A randomised-controlled trial (RCT) found that a music therapy singing group improved quality of life and affect in PLWD in long-term care settings, more than a "music medicine listening group" (Cho, 2018). In contrast, a systematic review of music therapy for dementia found music listening to have the greatest effect on patients, followed by singing (Moreno-Morales et al, 2020). Individualised singing interventions facilitated by family carers at home can reduce symptoms of depression and improve mood in PLWD, and increase family carer well-being, compared with usual care (Särkämö et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation